ANALISIS PENGARUH MEKANISME INTERNAL DAN EKSTERNAL CORPORATE GOVERNANCE TERHADAP PERSISTENSI LABA - Junawatiningsih, Tri; Harto, Puji (Faculty of Economics and Business Diponegoro University, 2014)
This research aims to analyze the affect of internal and external corporate governance mechanism on earning persistence. Earnings persistence is defined as the profit that can be used as an indicator of future earnings, in other words, the persistence of the earnings of a company's ability to survive in the future. Variabel independent used in this study is Internal corporate governance mechanisms (ownership concentration, institutional ownership, and audit committe) and external corporate governance mechanisms (audit tenure, industry specialize audit firm, and leverage). The dependent variabel used in this study is earning persistence in observations 2012 and 2013. The population of this research is 132 companies in the manufacturing sector which were listed in Indonesian Stock Exchange (IDX). The research data were collected from manufacturing companies financial statement for the period of 2012 and 2013. Based on purposive sampling method, there are 98Â samples. The reseacrh hypotesis were tested using multiple linear regression analysis. The results of this research showed that ownership concentration, audit commite, leverage and industry specialize audit firm has positive and significant effect on earning persistence. While institutional ownership and audit tenure has no significant effect on earning persistence.